The Effect Of Financial Performance, Good Corporate Governance, Asset Structure, Dividend Policy On Debt Policy - Brechmans Aditia Jogo Boro; Lucky Nugroho; Yananto Mihadi Putra; Anees Janee Ali (Baca Dulu Publisher, 2024)
This study aims to examine the effect of Financial Performance, Good Corporate Governance, Asset Structure and Dividend Policy on Debt Policy. The sample used in this study used companies incorporated in the LQ-45 index listed on the Indonesia Stock Exchange (IDX) in the period 2017 to 2022. The number of samples used was 108. The sample method used in this study was purposive sampling, while the data analysis used was regression of panel data using the SPSS program. The results of this study show that Return On Assets, Return On Equity (ROE), Institutional Ownership (IP) have a significant effect on debt policy, while Managerial Ownership (KM), asset structure (SA) and dividend payment ratio (DPR) do not have a significant effect on debt policy.